PERBEDAAN SIKAP, KETERAMPILAN, DAN PENGETAHUAN TENTANG PEDULI LINGKUNGAN PADA SISWA SEKOLAH DASAR PEDESAAN DAN PERKOTAAN MELALUI MODEL PJBL BERBASIS PENDEKATAN SAINTIFIK DI BENGKULU - Karjiyati, Victoria; Dalifa, Dalifa; Hasnawati, Hasnawati; Agusdianita, Neza (ATTA`DIB, 2019)
This study discusses differences of opinion, skills and knowledge of students about the environment in elementary school that discusses the area by using the PjBL model in thematic learning by using science in Bengkulu. This research is quantitative research. The method used in this study is a quasi-experimental method. The design used was only the design of the pretest-posttest control group suitable. The population in this study were fifth grade students of SD Negeri in Bengkulu Province. The sample of this study was a class of urban representative experiment class is the fifth grade students in SDN 81 Kota Bengkulu, SDN 7 Rejang Lebong Regency and SDN 16 Kabupaten Bengkulu Utara. The sample for the control class is the area of SDN 05 Lebong Regency, SDN 27 Kabupaten Bengkulu Tengah and SDN 013 Seluma Regency. Data analysis techniques used quantitative analysis techniques using the Mann Whitney-u test. Hypothesis test results obtained for the ability of knowledge, skills and attitudes of 0,000 <sig 0,025. The conclusions of this study are about differences of opinion, skills and knowledge about the environment in the elementary school that discusses the region and region using the PjBL model in thematic learning using scientific in Bengkulu.